Indonesia’s Political Shifts: From Opposition to Coalition in 2014–2024 Elections - Rizal Al Hamid (Jurnal Ilmu Kepolisian, 2025)
This paper explores the evolving trajectory of political alignments in Indonesia’s presidential elections between 2014 and 2024, focusing on the strategic transformation of political parties from opposition to coalition. Drawing on William H. Riker’s Minimal Winning Coalition theory, it argues that party behavior is shaped not only by electoral calculus but also by the broader objective of maintaining systemic stability. While Riker emphasizes efficiency through minimal coalitions, Indonesian coalitions are often expansive, serving as tools for mitigating political volatility rather than maximizing efficiency. Through a descriptive-analytical method based on secondary literature, this research finds that coalitions in Indonesia prioritize inclusive governance, often at the cost of a weakened opposition. Notable examples include the integration of PAN into Jokowi’s administration in 2015 and Gerindra’s cabinet entry after 2019. While this approach supports continuity and governance stability, it also raises concerns about the dilution of critical oversight. Ultimately, the study underscores how Indonesian coalitional politics reflect a pragmatic balance between power consolidation and democratic legitimacy.